Arabic Language Teachers’ Strategies for Developing Students’ Speaking Skills through Thematic Hadith Discussions - Nawawi, Mahbub; Basith, Abdul; Insaniyah, Anyes Lathifatul; Firdaus, Rousul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Developing speaking skills (maharah al-kalam) among Arabic learners remains a persistent challenge, particularly in Islamic secondary schools where communicative competence often lags behind receptive abilities. This study addresses the problem of how to effectively engage students in spoken Arabic by examining the integration of theme-based hadith discussions into classroom practice. The aim is to investigate how teachers at MAN 2 Banyuwangi design, implement, and evaluate such activities, and to assess their impact on students’ participation and fluency. Employing a qualitative approach within an intrinsic case study framework, the research collected data through classroom observations, semi-structured interviews, and document analysis, enabling triangulation of findings across multiple sources. The distinctive contribution of this work lies in its focused linkage between the moral and social themes of hadith and targeted speaking skill development, alongside a detailed analysis of teachers’ day-to-day instructional strategies. Results indicate that approaches such as linguistic scaffolding, contextual role-play, and small-group discussions anchored in selected hadith topics elevated student participation to approximately 90% and improved speaking fluency by 67%. Furthermore, the use of the ADDIE instructional design cycle ensured systematic planning, execution, and evaluation, enhancing both student engagement and language outcomes. This study contributes practical, evidence-based strategies for Arabic language instruction in Islamic educational contexts, demonstrating that selecting relevant themes, employing interactive methods, and applying structured pedagogical models can significantly advance speaking proficiency while reinforcing moral education.